Diagnóstico Serológico de Brucelosis en rebaños de Alpacas en la localidad de Huasillama. Guacapiña Camacho Edgar Arturo; Diagnóstico Serológico de Brucelosis en rebaños de Alpacas en la localidad de Huasillama. - Guacapiña Camacho, Edgar Arturo (2017)
This research was conducted in The National Research Institute of the Ecuador. The objective was to determine the presence of brucellosis in alpacas herds located in Huasillama using the Rose Bengal serological test. In this study was used previous Ecuadorian and abroad information from similar studies, which played an important role as an inquiry guide in order to discuss appropriately the required information with different contrasts. On the exploration field were obtained samples from 40 animals, from each animal was taken 5 ml of blood from the femoral vein and then the samples were analyzed with the agglutination method. The results after using the Rose Bengal serological test were 1 positive animal (+) and 39 negative (-). Through the calculation of the data was determined that as a 2.5% of the total camelids analyzed are infected. According to the obtained results and based on the current legislation law of Agroquality, Public Institution of Ecuador, it was proposed the implementation of a strategic plan in order to prevent and control this brucellosis through the application of vaccines in order to decrease the dissemination of this disease and improve public health.